2020
DOI: 10.3389/fonc.2020.01008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related Prognostic Biomarkers Based on the Tumor Microenvironment in 20 Malignant Tumor Types With Poor Prognosis

Abstract: Cancer, especially malignant tumors with poor prognosis, has become a major hazard to human life and health. The tumor microenvironment is gaining increasing attention from researchers, as it offers a new focus for tumor diagnosis, therapy, and prognosis. The numbers of immune and stromal cells, which are major components of the tumor microenvironment, could be determined from RNA-seq data with the Estimation of STromal and Immune cells in Malignant Tumors using Expression data (ESTIMATE) algorithm. To explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Among them, low C16orf54 expression was considered to be a risk factor for SKCM, LUAD, CESC, and other tumours. Liu et al report that C16orf54 expression levels were associated with BRCA, LUAD, LGG, and SKCM prognosis, but it remains unclear whether low or high C16orf54 expression is a prognostic risk factor [24]. The above results show that C16orf54 is a potential marker of the poor prognosis of various tumours, further suggesting that C16orf54 participates in the progression of tumours.…”
Section: Discussionmentioning
confidence: 79%
“…Among them, low C16orf54 expression was considered to be a risk factor for SKCM, LUAD, CESC, and other tumours. Liu et al report that C16orf54 expression levels were associated with BRCA, LUAD, LGG, and SKCM prognosis, but it remains unclear whether low or high C16orf54 expression is a prognostic risk factor [24]. The above results show that C16orf54 is a potential marker of the poor prognosis of various tumours, further suggesting that C16orf54 participates in the progression of tumours.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, broad identification of general immune microenvironments may be more effective than relying on the identification of individual levels of biomarker genes when analyzing immune-related survival rates. 15 , 16 Thus, CIBERSORT, a popular TIL prediction method, was selected. Through the LM22 signature matrix, CIBERSORT provided the most diverse predictions of abundance levels across TIL subsets among the tumor microenvironment (TME) deconvolution tools that were currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumor tissues include not only tumor cells, but also supportive tumor-associated healthy cells (stromal cells and immune cells), which comprise the tumor microenvironment (TME) ( 5 ). The TME has recently attracted increasing attention, as it provides a novel context for tumor diagnosis and prognosis ( 6 ). The TME also provides essential cues to maintain stemness and promote the seeding of tumor cells at sites of metastasis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of stromal and immune cells in malignant tumors using expression data (ESTIMATE) algorithm can be used to estimate and quantify the TME. Many studies ( 6 8 ) have shown that stromal score, immune score, and tumor purity measurements based on the TME can serve as prognostic tumor biomarkers. For HCC, immunohistochemical scoring of CD38 molecule in the TME can be used to predict responsiveness to anti-programmed cell death 1/CD274 molecule (i.e., anti-PD-1/PD-L1) immunotherapy ( 9 ).…”
Section: Introductionmentioning
confidence: 99%